She Sells Seashells - Kim, Grace; Nang Chan Yeema (New York, USA Scholastic Inc., 1995)
Peter Piper and Silly Sally visit Betty Botter, reciting well-known tongue twisters along the way.
Keywords: Juvenile Fiction